Biochemical studies of Circumoncobothrium (Shinde 1968) tapeworm in freshwater fish Mastacembelus armatus - Kaldate, K D; Wankhede, H J; Aade, U P (International Multidisciplinary Research Journal, 2012)
Parasitic biochemistry has great practical importance through chemotherapy and vaccine production and in understanding of the complex association involved in the host parasite relationship However; information in parasite biochemistry is patchy. The present study deals with the biochemistry (Protein, glycogen, lipid) of parasites circumoncobothrium in fresh water fish Mastacembelus armatus, Collected from fresh water fish. circumoncobothrium parasites are the most pathogenic cestode parasites.